Information technology for supporting the development and maintenance of open innovation capabilities - Emmanuel Adamides; Nikos Karacapilidis (Journal of Innovation & Knowledge (JIK), 2020)
We discuss ICT for Open Innovation (OI) from a capabilities perspective. We distinguish two types of capabilities for OI: strategic, which need to be developed so that the organization can take advantage of an OI strategy proactively, and operational for the efficient implementation of OI processes. ICT at the strategic level supports dynamic capabilities and related cognitive processes of managerial staff for developing and using the appropriate level of absorptive capacity and active transparency, whereas ICT as part of operational capabilities aims at enhancing the day-to-day performance of OI activities. Through analysis of capabilities, we associate specific ICT with the functionalities required in the entire OI process. Paying particular attention to the issues of collaboration and sophisticated data analysis, we also comment on the seamless integration of these technologies and their embedment in OI-related organizational processes.
Keywords: 650; Capabilities; Collective and collaborative intelligence; ICT; Knowledge engineering and management; Open innovation